2020
DOI: 10.1111/cdev.13392
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Iconic Gesture Promotes First‐ and Second‐Order Verb Generalization in Preschoolers

Abstract: This study investigated whether seeing iconic gestures depicting verb referents promotes two types of generalization. We taught 3-to 4-year-olds novel locomotion verbs. Children who saw iconic manner gestures during training generalized more verbs to novel events (first-order generalization) than children who saw interactive gestures (Experiment 1, N = 48; Experiment 2, N = 48) and path-tracing gestures (Experiment 3, N = 48). Furthermore, immediately (Experiments 1 and 3) and after 1 week (Experiment 2), the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Second, our study is the first to show an effect of function training on second-order generalization. Thus, it expands the existing literature on how to facilitate second-order generalization (Aussems & Kita, 2021;Perry et al, 2010;Samuelson, 2002;Smith et al, 2002;Ware & Booth, 2010). Third, and most importantly, our results show that 19-month-olds are cognitively ready to use function for word learning.…”
Section: Function Training Promotes First-and Second-order Noun Generalizationsupporting
confidence: 80%
“…Second, our study is the first to show an effect of function training on second-order generalization. Thus, it expands the existing literature on how to facilitate second-order generalization (Aussems & Kita, 2021;Perry et al, 2010;Samuelson, 2002;Smith et al, 2002;Ware & Booth, 2010). Third, and most importantly, our results show that 19-month-olds are cognitively ready to use function for word learning.…”
Section: Function Training Promotes First-and Second-order Noun Generalizationsupporting
confidence: 80%
“…For example, if a caregiver used highly iconic words like STICKY, SPIKY, or TAP to describe an object's texture, shape, or function, it could help draw the child's attention to the object and its features. Indeed, previous studies of novel action encoding reveal that iconic gestures facilitate children's memory of those actions (Aussems & Kita, 2019) and their labels (Aussems & Kita, 2020). More generally, cues that draw attention to an object and its features, including social cues such as pointing (Horst & Samuelson, 2008), or visual cues such as flashing lights (Axelsson, Churchley, & Horst, 2012), help children form word-referent associations and remember them later.…”
Section: A Developmental Cascade Account Of Iconicitymentioning
confidence: 97%
“…First, Mumford and Kita (2014) showed that 3-year-old children use iconic gestures to interpret novel verb meanings. Furthermore, Aussems and Kita (2021) showed that children use iconic gestures not only to interpret individual verb meanings, but also to learn more novel verbs from the same category, even when iconic gestures are absent. Thus, iconic gesture helped children to create general knowledge for how to learn verbs of the same category which they could use later.…”
mentioning
confidence: 99%